Acute Appendicitis on Computed Tomography: Findings, Pitfalls, Complications, and Mimics (International Journal of Radiology and Imaging, 2025)
Acute appendicitis is one of the most common causes of abdominal pain. It is largely a clinical diagnosis, while imaging may be employed to aid diagnosis. Unfortunately, establishing a diagnosis of acute appendicitis based on imaging is challenging. We present computed tomography findings, pitfalls, complications, and mimics of acute appendicitis.